2022
DOI: 10.1001/jamapsychiatry.2022.0301
|View full text |Cite
|
Sign up to set email alerts
|

Association of Task-Shared Psychological Interventions With Depression Outcomes in Low- and Middle-Income Countries

Abstract: This is a repository copy of Association of task-shared psychological interventions with depression outcomes in low-and middle-income countries : a systematic review and individual patient data meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Implementation strategies should include competency-based training, supervision and support for maternity staff and other frontline providers to provide primary-level mental healthcare (Honikman et al ., 2012 , Lund et al ., 2014 , Howard et al ., 2014 , WHO, PEPFAR & UNAIDS, 2007 ). Linked to this, investments should be made to create remunerated staff positions for non-specialist mental health providers in maternal and child service and community-based settings (Jacobs et al ., 2021 ; Karyotaki et al ., 2022 ; Patel, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Implementation strategies should include competency-based training, supervision and support for maternity staff and other frontline providers to provide primary-level mental healthcare (Honikman et al ., 2012 , Lund et al ., 2014 , Howard et al ., 2014 , WHO, PEPFAR & UNAIDS, 2007 ). Linked to this, investments should be made to create remunerated staff positions for non-specialist mental health providers in maternal and child service and community-based settings (Jacobs et al ., 2021 ; Karyotaki et al ., 2022 ; Patel, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even after controlling for factors such as smoking status, gender, weight, activity level, blood pressure, and cholesterol levels, the findings of another study [32] showed that depression contributes to a greater chance of developing or dying of heart disease in people who are otherwise healthy. This was the case regardless of whether or not the participants smoked.…”
Section: Discussionmentioning
confidence: 96%
“…In conclusion, the findings are consistent with other research on the global scale on the task-sharing issue. 33 Therefore, perhaps it is promising to invest more in the task-sharing approach combined with internet intervention (e.g., internet-based cognitive behavioral therapy, guided or unguided) to address the treatment gap issue faced by the country. 34 There has also been a growing discussion of using an "indirect approach" to prevent and treat depression by aiming the intervention on daily problems related to depression, such as insomnia, perfectionism, and procrastination.…”
Section: Pandemic Young People and Increasing Awareness Of Mental Healthmentioning
confidence: 99%